2017
DOI: 10.1287/mnsc.2015.2369
|View full text |Cite
|
Sign up to set email alerts
|

Does Lean Improve Labor Standards? Management and Social Performance in the Nike Supply Chain

Abstract: This study tests the hypothesis that lean manufacturing improves the social performance of manufacturers in emerging markets. We analyze an intervention by Nike Inc. to promote the adoption of lean manufacturing in its apparel supply chain across eleven developing countries. Using difference-indifferences estimates from a panel of over three hundred factories, we find that lean adoption was associated with a 15 percentage point reduction in noncompliance with labor standards that primarily reflect factory wage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
191
2
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(201 citation statements)
references
References 65 publications
(89 reference statements)
3
191
2
5
Order By: Relevance
“…This measure captures a particular version of capability building that relied on off‐site managerial training, rather than directly engaging suppliers on the factory floor (Sako , Distelhorst et al . ), and focused entirely on China, where code violations were most prevalent.…”
Section: Institutional Versus Factory‐level Explanationsmentioning
confidence: 99%
“…This measure captures a particular version of capability building that relied on off‐site managerial training, rather than directly engaging suppliers on the factory floor (Sako , Distelhorst et al . ), and focused entirely on China, where code violations were most prevalent.…”
Section: Institutional Versus Factory‐level Explanationsmentioning
confidence: 99%
“…Future research should examine industry-level trends. Arguably, the transmission of such cost pressures is likely to vary across different types of value or commodity chains (Gereffi and Frederick, 2010), and across firms even within a given industry (Distelhorst et al 2016). For example, this transmission might be more likely when buyers and customers are linked via shortterm contracts (e.g., textile industries) instead of longer-term contracts (e.g., heavy manufacturing).…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have shown that civil society and state regulatory mechanism can complement CSR programmes when they are strong, but the impact of CSR tends to be hampered in countries such as China due to state policies that do not sanction independent union formation (Distelhorst et al. ; Locke et al. ).…”
Section: Corporate Social Responsibility and Workers’ Rightsmentioning
confidence: 99%